"One Country, Two Systems": A Corpus-assisted Discourse Analysis of the Politics of Recontextualization in British, American and Chinese Newspapers. Issue 3 (4th May 2021) - Liu, Ming; Lin, Ling
ABSTRACT: This study gives a corpus-assisted discourse study of the recontextualization of "One Country, Two Systems" in Chinese, British and American newspapers. It proposes to analyse the recontextualization of "One Country, Two Systems" at four levels: (1) Lexicalization; (2) Grammatical functions; (3) Evaluation; and (4) Perspectivation. The findings show not only the systematic differences between Chinese and Anglo-American newspapers but also the subtle differences between American and British newspapers in their specific ways of recontextualization. It is argued that a proper understanding of the politics of recontextualization should explicate the dynamic relations between media systems, national interests, and the specific ways of recontextualization.